1385 Optimizing Nutrition After Birth with a Unique Standardized Parenteral Solution May Reduce Electrolytes Anomalies in < 1250G Infants. (October 2012) - Senterre, T; Rigo, J
Abstract : Nutritional recommendations in VLBW infants advised to increase protein and energy intakes but also advised to avoid parenteral nutrition electrolytes intakes during the first 2–3 days of life to reduce electrolytes anomalies that are frequently observed. The Aim: of this study is to evaluate the electrolytes tolerance of an optimized nutritional program using a unique standardized parenteral nutrition solution (StPNsol) containing electrolytes from the first day of life in < 1250g infants (N=102) during the first 15 days of life. On the first day of life, PN intakes from the StPNsol included 38±6 kcal/kg*d, 2.4±0.3 g/kg*d of protein, 0.8±0.4 mmol/kg*d of sodium and 0.8±0.4 mmol/kg*d potassium. Afterwards, nutritional intakes rapidly increased. Hypernatremia >150 mmol/L occurs in 16 infants (15.6%), on 27 days (1.8%), essentially between 1 and 3 days of life (19 days). Hyponatremia < 130 mmol/L occurs in 31 infants (30.4%) on 55 days (3.6%), essentially between 1 and 7 days of life (40 days). No infant develops a hyperkaliemia >7 mmol/L. Hypokaliemia < 3 mmol/L occurs in 9 infants (8.8%) on 16 days (1.0%), mainly between 1 and 3 days of life (7 days). This study demonstrates that increasing protein and energy intakes with a StPNsol containing electrolytes from the first day of life is not associated with an increased incidence of hypernatremia or non-oliguric hyperkaliemia. Furthermore, this study seem to suggest that optimizing nutritional intakes and increasing anabolism may require higher electrolytes intakes than usually recommended during the first days of life in VLBW infants.